Deficiency of mastl, a mitotic regulator, results in cell detachment from developing tissues of zebrafish embryos - Utsumi, Hideko; Yabe, Taijiro; Koshida, Sumito; Yamashita, Akira; Takada, Shinji (Frontiers in Cell and Developmental Biology, 2024)
To form tissues with unique functions and structures, it is important that the cells that comprise them maintain physical contact. On the other hand, with each mitosis, drastic changes in cell shapes, cell adhesion, and cytoskeletal architecture may cause such contacts to be temporarily weakened, risking improper development and maintenance of tissues. Despite such risks, tissues form properly during normal development. However, it is not well understood whether mitotic abnormalities affect tissue formation. Here, analysis of zebrafish embryos with aberrant mitosis shows that proper progression of mitosis is important to maintain cell contact in developing tissues. By screening mutants with abnormal trunk and tail development, we obtained a mutant with perturbed expression of some tissue-specific genes in embryonic caudal regions. The responsible gene is mastl/gwl, which is involved in progression of mitosis. Analysis focusing on the chordo-neural hinge (CNH), the primordium of axial tissues, shows that cell detachment from the CNH is increased in mastl mutant embryos. Time-lapse imaging reveals that this cell detachment occurs during mitosis. These results suggest that cells are unable to maintain contact due to abnormalities in progression of mitosis in mastl mutants.